Design and construction of A 1 MeV cyclotron - Şimşek, Ebru. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This thesis studies the design and construction of Turkey’s ﬁrst 1 MeV cyclotron. The iron yoke, electromagnets and vacuum chamber, which are its main components, have been constructed. Electrically insulated electromagnets have been assembled using copper proﬁle pipes at the ¨Ozyeg˘in University Particle Accelerator Laboratory. Applying a direct current to magnet coils, an almost uniform magnetic ﬁeld has been achieved between the poles. Magnetic ﬁeld values obtained from the simulations are compatible with measured magnetic values. Furthermore, betatron oscillations have been observed in the ion path simulation computed with the 4th order Runge Kutta method. Near future goals are the connection of a custom-designed RF power ampliﬁer and the measurement of ﬂow parameters which have already been calculated for the cooling system.
Keywords: Cyclotrons.